eCM 2021
DOI: 10.22203/ecm.v041a40
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hyaluronate supplemented culture medium combined with joint-simulating mechanical loading improves chondrogenic differentiation of human mesenchymal stem cells

Abstract: In vitro models aim to recapitulate the in vivo situation. To more closely mimic the knee joint environment, current in vitro models need improvements to reflect the complexity of the native tissue. High molecular weight hyaluronan (hMwt HA) is one of the most abundant bioactive macromolecules in healthy synovial fluid, while shear and dynamic compression are two joint-relevant mechanical forces. The present study aimed at investigating the concomitant effect of joint-simulating mechanical loading (JSML) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(50 reference statements)
1
3
0
Order By: Relevance
“… 20 Similarly, COL2A1 also increased due to mechanical loading, and while not statistically significant (due to non-detected gene expression in UL), the highest gene expression values were reproducibly found in samples loaded within the MWB. Moreover, as shown within our previous 4-station bioreactor, 12 , 21 mechanical stimulation increased PRG4 expression, a mechano-regulated protein that contains sGAGs and plays an important role in the lubrication of articular joints. 22 …”
Section: Discussionsupporting
confidence: 75%
“… 20 Similarly, COL2A1 also increased due to mechanical loading, and while not statistically significant (due to non-detected gene expression in UL), the highest gene expression values were reproducibly found in samples loaded within the MWB. Moreover, as shown within our previous 4-station bioreactor, 12 , 21 mechanical stimulation increased PRG4 expression, a mechano-regulated protein that contains sGAGs and plays an important role in the lubrication of articular joints. 22 …”
Section: Discussionsupporting
confidence: 75%
“…Surprisingly little is known on the mechano-competence of MSC-derived chondrocytes. Most in vitro studies applying mechanical loading to MSC-based tissue engineering constructs investigated whether load can enhance the efficiency of chondrogenic conversion to replace essential pro-chondrogenic factors like transforming growth factor (TGF)-β [ 10 16 ]. Alternatively, it was attempted to reproduce the physical microenvironment in the joint to increase the mechanical stability of MSC-derived neocartilage [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…). According to Altman and other scholars, intraarticular injection of sodium hyaluronate can reduce cartilage catabolism activity, and then reduce chondrocyte apoptosis and increase chondrocyte proliferation, thus inhibit the role of pro-inflammatory mediators and pain mediators[ 17 ]. This study showed that the excellent and good rate of rehabilitation in the group A was raised than group B.…”
Section: Discussionmentioning
confidence: 99%